2020
DOI: 10.1051/meca/2020066
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigations of vibration and acoustics signals in milling process using kapok oil as cutting fluid

Abstract: Vegetable oils are found as the feasible alternative for conventional minerals oils. There has been many environmental and health issues which are spotted with the use of conventional cutting fluids. There has been a great demand for developing new environmentally friendly vegetable based cutting fluids to reduce these harmful effects. In this present study, vegetable based kapok oil is used as a cutting fluid during milling to study its consequences over other conventional oils. The process parameters such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The higher molecular weight and boiling point of vegetable oils reduce their vaporization process [42]. For all those benefiting features of vegetable oils, many of them are used as cutting fluids in cutting process like kapok oil [43], olive oil [44], and sunflower oil [45].…”
Section: B2 Vegetable Oilsmentioning
confidence: 99%
“…The higher molecular weight and boiling point of vegetable oils reduce their vaporization process [42]. For all those benefiting features of vegetable oils, many of them are used as cutting fluids in cutting process like kapok oil [43], olive oil [44], and sunflower oil [45].…”
Section: B2 Vegetable Oilsmentioning
confidence: 99%
“…Vegetable oils have shown the nest prospects as alternative base oil. This is due to their high biodegradability, renewability, minimal toxicity, wide availability, high ash-point, high viscosity index, good lubricity, and promising vibrationdamping characteristics [22][23][24][25]. Among thickeners, modi ed cellulose [26][27][28][29] and organoclays [29][30][31] have been the two extensively tried and successful options.…”
Section: Introductionmentioning
confidence: 99%
“…It was identified that acoustic emission varies linearly with the cutting velocity. Shankar et al [12] carried out an experimental study on influence of different cutting fluids in the acoustic pressure during milling of mild steel. It was revealed that acoustic pressure is maximum while using Kapok oil compared to Mineral oil or Palm oil.…”
Section: Introductionmentioning
confidence: 99%